Cobalt-doped zinc oxide nano-catalyst as well as preparation method and application thereof

The local dipoles are constructed through cobalt-doped zinc oxide nanocatalysts and activated PMS, solving the problem of difficulty in removing electron-rich pollutants in the prior art, and achieving efficient and stable pollutant removal and water quality improvement.

CN119746870AActive Publication Date: 2025-04-04NANKAI UNIV

Patent Information

Application Number
CN202510016468.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-04
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove electron-rich pollutants, especially in complex water bodies. In addition, traditional pre-oxidation processes have problems such as foul odor and sludge generation, making it difficult to meet strict water quality emission standards.

Method used

Co-doped zinc oxide nanocatalyst is used to break the charge symmetry of ZnO through Co-doping, build local dipoles, promote PMS activation, and improve the efficiency of pollutant removal.

Benefits of technology

100% removal of para-aniline was achieved, with a maximum reaction rate constant of 1.6351 min-1, which has stable degradation performance and high selectivity, and significantly improves the removal effect of electron-rich pollutants, while reducing biotoxicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746870A_ABST
    Figure CN119746870A_ABST
Patent Text Reader

Abstract

The invention discloses a cobalt-doped zinc oxide nano-catalyst as well as a preparation method and application thereof. The preparation method of the cobalt-doped zinc oxide nano-catalyst comprises the following steps: dissolving zinc salt and citric acid in deionized water, adding cobalt salt, uniformly mixing, stirring at the room temperature of 15-25 DEG C to obtain sol liquid, reacting the sol liquid at the temperature of 70-80 DEG C to obtain wet gel, drying and grinding the wet gel at the temperature of 160-180 DEG C to obtain precursor powder, and preparing the cobalt-doped zinc oxide nano-catalyst in an air atmosphere to obtain the cobalt-doped zinc oxide nano-catalyst. And calcining the precursor powder at 480-520 DEG C for 5-5.5 h, washing, and drying to obtain the cobalt-doped zinc oxide nano catalyst. The cobalt-doped zinc oxide nano-catalyst can efficiently activate PMS, 100% of aniline can be removed within 5 min, and the cobalt-doped zinc oxide nano-catalyst has high anti-interference capacity and stability and has stable degradation performance in different coexisting ions and wide pH ranges.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and specifically relates to a cobalt-doped zinc oxide nanocatalyst and a preparation method and application thereof. Background Art

[0002] With population growth, industrial development and climate change, freshwater shortage has become a global challenge, affecting about 4 billion people worldwide, and this problem may be further exacerbated in the near future. Chemicals containing electron donating groups (EDGs) such as -OH and -NH2 are widely used in modern industry due to their good chemical reactivity, biocompatibility and functionalization ability, especially in industrial parks with intensive industrial activities. Therefore, industrial parks also produce a large amount of wastewater with high concentrations of electron-rich pollutants (e-RNPs) rich in electron donating groups. Although this wastewater can be diluted to a certain extent by the urban pipeline network, the electron-rich pollutants in it are still difficult to be removed by the urban sewage treatment system and cause significant harm to subsequent biological treatment structures.

[0003] Traditional pre-oxidation processes based on hydrolysis and acidification can effectively reduce e-RNPs in wastewater, improve the biodegradability of wastewater, and reduce biological toxicity. However, due to the long hydraulic retention time and sensitivity to environmental conditions (such as temperature and pH value), it is easy to produce odor and a large amount of sludge, making it difficult to meet the increasingly stringent water discharge standards. Therefore, it is urgent to use advanced treatment processes to treat electron-rich pollutants containing electron-donating groups to increase the supply of fresh water outside the hydrological cycle to alleviate the water crisis.

[0004] In recent years, potassium persulfate (PMS) advanced oxidation technology has been widely used because it can produce strong oxidative free radicals (such as sulfate and hydroxyl radicals) and selective non-free radicals (such as singlet oxygen 1O2) is highly favored because it can quickly oxidize difficult-to-degrade organic pollutants, has high system stability, and does not produce secondary pollution. However, coexisting ions in complex water bodies can hinder the generation of non-selective free radicals or cause false attacks, and the single non-free radicals have insufficient oxidation performance and ultra-short lifespan (about 2 to 4 microseconds) in water, which limits the degradation of target pollutants. Xu (Jiang, X.; Zhou, B.; Yang, W.; Chen, J.; Miao, C.; Guo, Z.; Li, H.; Hou, Y.; Xu, X.; Zhu, L.; et al. Precise coordination of high-loading Fe single atoms with sulfur boosts selective generation of nonradicals.Proc.Natl.Acad.Sci.USA2024,121(4),e2309102121.) et al. significantly increased the production of high-valent iron oxide species and singlet oxygen by precisely regulating the short-range S coordination of Fe single atoms. However, they rely on single-atom catalysts to achieve two or more pathways, which is limited by the electron circulation of a single active metal center and the efficiency of substrate electron transfer. The synergistic effect of multiple catalytic pathways is difficult to control, thus affecting the further improvement of catalytic activity. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a cobalt-doped zinc oxide nanocatalyst, which breaks the original charge symmetry of ZnO through Co doping, thereby constructing localized dipoles in the adjacent Zn and Co atomic site regions, promoting PMS activation and improving the removal of pollutants.

[0006] Another object of the present invention is to provide a method for preparing a cobalt-doped zinc oxide nanocatalyst.

[0007] Another object of the present invention is to provide an application of a cobalt-doped zinc oxide nanocatalyst in removing pollutants.

[0008] The purpose of the present invention is achieved through the following technical solutions.

[0009] A method for preparing a cobalt-doped zinc oxide nanocatalyst comprises the following steps:

[0010] Step 1, dissolving zinc salt and citric acid in deionized water, adding cobalt salt and mixing evenly, stirring at room temperature of 15-25° C. for 1-1.5 hours to obtain a sol liquid, reacting the sol liquid at 70-80° C. for 3-4 hours to obtain a wet gel, drying the wet gel at 160-180° C. for 3-3.5 hours, grinding, and obtaining a precursor powder, wherein, by amount of substance, the ratio of zinc in the zinc salt, cobalt in the cobalt salt, and citric acid is 15: (0.75-1.05): 45;

[0011] In step 1, the volume ratio of the amount of zinc in the zinc salt to the volume ratio of deionized water is 1:

[0012] (25~35), the unit of the amount of the substance is mmol, and the unit of the volume is mL.

[0013] In step 1, the zinc salt is zinc nitrate hexahydrate, and the cobalt salt is cobalt nitrate hexahydrate.

[0014] In the step 1, the grinding time is 4 to 6 minutes.

[0015] Step 2: calcining the precursor powder at 480-520° C. for 5-5.5 h in an air atmosphere, washing, and drying to obtain a cobalt-doped zinc oxide nanocatalyst.

[0016] In the step 2, heating is performed to 480-520° C. at a rate of 4-6° C. / min.

[0017] In step 2, the washing operation includes: centrifuging at least three times with water and ethanol at a speed of 8000-10000 r / min, each centrifugation lasting 3-5 minutes.

[0018] In step 2, the drying temperature is 60 to 80° C., and the drying time is 10 to 12 hours.

[0019] The cobalt-doped zinc oxide nanocatalyst obtained by the preparation method.

[0020] The application of the above cobalt-doped zinc oxide nanocatalyst in removing pollutants.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The cobalt-doped zinc oxide nanocatalyst of the present invention can efficiently activate PMS by constructing a localized dipole, achieving 100% aniline removal within 5 minutes, with a maximum reaction rate constant of 1.6351 min -1 .

[0023] 2. The cobalt-doped zinc oxide nanocatalyst of the present invention has strong anti-interference ability and has stable degradation performance in different coexisting ions and a wide pH range.

[0024] 3. The cobalt-doped zinc oxide nanocatalyst of the present invention has excellent selectivity for electron-rich pollutants containing electron-donating groups, which can greatly improve the biodegradability of sewage while reducing biological toxicity.

[0025] 4. The cobalt-doped zinc oxide nanocatalyst of the present invention has high stability, good structural integrity and low metal ion leakage in the process of efficient activation of PMS.

[0026] 5. The cobalt-doped zinc oxide nanocatalyst of the present invention can achieve the following in the process of activating PMS to remove electron-rich pollutants: 1 O2 and Co IV =O Selective production of two species. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 (a) TEM image, (b) high-resolution transmission electron microscopy (HRTEM) and (c) elemental mapping image of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3;

[0028] Figure 2 are X-ray diffraction patterns, (a) is the zinc oxide catalyst prepared in Comparative Example 1 and the cobalt-doped zinc oxide nanocatalyst prepared in Example 3, (b) is the Co-doped ZnO catalyst prepared in Comparative Example 2;

[0029] Figure 3 Graph showing removal efficiency, (a) for PMS, the zinc oxide catalyst prepared in Comparative Example 1, and the cobalt-doped zinc oxide nanocatalyst prepared in Example 3, (b) for the cobalt-doped zinc oxide nanocatalyst prepared in Examples 1 to 4;

[0030] Figure 4 is the removal rate of aniline by the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 under different coexisting ions;

[0031] Figure 5 are the removal rate and reaction rate constant of aniline by the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 at different pH values;

[0032] Figure 6 The removal rate of different pollutants by the cobalt-doped zinc oxide nanocatalyst prepared in Example 3;

[0033] Figure 7 Three-dimensional excitation emission matrix (3D-EEM) fluorescence spectra, (a) is the actual sewage before the pollutant removal experiment, (b) is the actual sewage after the pollutant removal experiment;

[0034] Figure 8 The Co doped ZnO nanocatalyst prepared in Example 3 and the Co doped ZnO catalyst prepared in Comparative Example 2 are 2+ Leakage

[0035] Fig. 9 The removal efficiency of aniline by the cobalt-doped zinc oxide nanocatalyst prepared in Example 3, the Co-doped ZnO catalyst prepared in Comparative Example 2, and cobalt nitrate hexahydrate;

[0036] Fig.10 (a) is the catalyst group and the PMS group to activate PMS to produce 1 The EPR spectrum of O2, Fig.10 (b) is the PMSO consumption diagram of the catalyst group and the PMS group at different times;

[0037] Fig.11 (a) is the ELF calculation diagram of the zinc oxide catalyst prepared in Comparative Example 1, Fig.11 (b) is the ELF calculation diagram of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3, Fig.11 (c) is a diagram showing the dipole effect. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0039] In the following examples, the drugs, molecular formulas, purities and purchasing manufacturers involved are shown in Table 1.

[0040] Table 1

[0041]

[0042] In the following examples, the instruments, models and manufacturers involved are shown in Table 2.

[0043] Table 2

[0044]

[0045]

[0046] Embodiments 1 to 4

[0047] A method for preparing a cobalt-doped zinc oxide nanocatalyst comprises the following steps:

[0048] Step 1, dissolving zinc salt and citric acid in deionized water, adding cobalt salt and mixing evenly, stirring with a magnetic stirrer at room temperature of 15-25°C for 1h to obtain a sol liquid, reacting the sol liquid in a 70°C water bath heating pot for 4h (part of the water evaporates) to obtain a wet gel, placing the wet gel in an electric constant temperature drying oven at 170°C for 3h (evaporating the water), grinding for 5min, and obtaining a precursor powder, wherein the zinc salt is zinc nitrate hexahydrate, the cobalt salt is cobalt nitrate hexahydrate, and the ratio of zinc in the zinc salt, cobalt in the cobalt salt and citric acid is W in terms of the amount of substance. The ratio of the amount of zinc in the zinc salt to the volume of deionized water is 1:25, the unit of the amount of substance is mmol, and the unit of the volume is mL.

[0049] Step 2, under air atmosphere, place the precursor powder in a muffle furnace, heat to 500°C at a rate of 5°C / min and calcine at 500°C for 5 hours, wash it with water and ethanol at a speed of 8000r / min for 3 times, each centrifugation time is 3 minutes, and dry it at 60°C for 10 hours after centrifugation to obtain a cobalt-doped zinc oxide nanocatalyst.

[0050] The W of the cobalt-doped zinc oxide nanocatalysts prepared in Examples 1 to 4 is shown in Table 3.

[0051] Table 3

[0052]

[0053]

[0054] Comparative Example 1

[0055] A method for preparing a zinc oxide catalyst (code: ZnO) is basically the same as that of Example 1, except that in the sol liquid, in step 1 of this comparative example, zinc salt (zinc salt is zinc nitrate hexahydrate) and citric acid are dissolved in deionized water, and stirred with a magnetic stirrer at room temperature of 15 to 25° C. for 1 hour to obtain a sol liquid, wherein, by molar mass, the ratio of zinc to citric acid in the zinc salt is 15:45.

[0056] Comparative Example 2

[0057] A method for preparing a Co-doped ZnO catalyst is disclosed in Example 1 of the Chinese invention patent publication number CN 113976125 A.

[0058] The morphology, crystal structure and element distribution of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 were characterized by transmission electron microscopy (TEM) and condenser spherical aberration corrected transmission electron microscopy (AC-TEM). Figure 1 As shown, Figure 1(a) TEM image, (b) high-resolution transmission electron microscopy (HRTEM) and (c) elemental mapping image of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3. Figure 1 From (a) and (b), it can be seen that Co is distributed as a single atom in the cobalt-doped zinc oxide nanocatalyst prepared in Example 3. Figure 1 As can be seen from (c), Zn, Co and O are uniformly distributed in the cobalt-doped zinc oxide nanocatalyst prepared in Example 3.

[0059] Figure 2 X-ray diffraction patterns, (a) for the zinc oxide catalyst prepared in Comparative Example 1 and the cobalt-doped zinc oxide nanocatalyst prepared in Example 3, (b) for the Co-doped ZnO catalyst prepared in Comparative Example 2. Figure 2 As shown in (a), the diffraction peaks of the zinc oxide catalyst prepared in Comparative Example 1 and the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 can be well matched with the standard card of zinc oxide (JCPD S 36-1451), wherein no characteristic peaks related to Co were found in the X-ray diffraction pattern of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3, mainly because Co exists in the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 in the form of single atoms and the content is relatively low. Figure 2 (b) shows that the Co-doped ZnO catalyst prepared in Comparative Example 2 has both the crystal structure of zinc oxide and cobalt oxide (with the JCPD of Co3O4 S 42-1467 standard card corresponding to the crystal structure, at the same angle, the peak intensity of the characteristic peak of the Co-doped ZnO catalyst prepared in Comparative Example 2 is lower than the peak intensity of the characteristic peak of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3, indicating that its crystallinity is greatly reduced. This may be the reason why the Co-doped ZnO catalyst prepared in Comparative Example 2 has an unstable structure and has an extremely high metal ion leakage.

[0060] Example 5

[0061] Pollutant removal experiment: 10 mg of catalyst, 15 mg of PMS and 50 mL of pollutant solution were placed in a 100 mL beaker to obtain a test solution. The test solution was stirred at 25 ° C for 5 min. 3 mL of the test solution was taken at Tmin to detect its absorbance, and the concentration (C) of the pollutant at Tmin was determined. T was 0 min, 0.5 min, 1 min, 2 min, 3 min, 4 min and 5 min, respectively. The catalyst was one of the cobalt-doped zinc oxide nanocatalysts prepared in Examples 1 to 4 and the zinc oxide catalyst prepared in Comparative Example 1. The pollutant solution was a mixture of pollutants and water. The pollutant was aniline. The initial concentration (C0) of the pollutant (aniline) in the pollutant solution was 10 mg / L. The pH of the pollutant solution was 7.0. The test results are as follows: Figure 3 As shown;

[0062] Control experiment: The control experiment is basically the same as the "pollutant removal experiment", except that the test solution in the control experiment does not contain a catalyst, that is, the preparation method of the test solution in the control experiment is: 15 mg PMS and 50 mL of pollutant solution are placed in a 100 mL beaker to obtain the test solution. The test results are as follows Figure 3 As shown in “PMS”.

[0063] Depend on Figure 3 As shown in (a), in the control experiment, the ability of PMS (without catalyst) to remove aniline is very weak, and the ability of zinc oxide catalyst prepared in Comparative Example 1 to remove aniline is also very weak. Figure 3 In (b), when the doping amount of Co increases, the removal efficiency of aniline by the cobalt-doped zinc oxide nanocatalysts prepared in Examples 1 to 4 gradually increases. The cobalt-doped zinc oxide nanocatalysts prepared in Examples 3 to 4 have the best removal efficiency for aniline, and the removal rate can reach 100% in 5 minutes.

[0064] Example 6

[0065] To further explore the stability and anti-interference ability of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3, the following experimental groups were set up:

[0066] Control group: The cobalt-doped zinc oxide nanocatalyst prepared in Example 3 was used as a "catalyst" to carry out the "pollutant removal experiment" in Example 5 above on the pollutant solution (aniline, pH 7). The removal rate is as follows: Figure 4 As shown in “control”;

[0067] Coexisting ion group: basically the same as the control group, except that the test solution was prepared by placing 10 mg of catalyst, 15 mg of PMS, salt and 50 mL of pollutant solution in a 100 mL beaker to obtain the test solution, wherein the salt was KCl (K was freed in the test solution). + as coexisting ions), CaCl2 (free Ca in the test solution 2+ as coexisting ions), NaCl (free Na + and Cl - as coexisting ions), MgCl2 (Mg is released in the test solution 2+ As coexisting ions, NH4Cl (NH4 is released in the test solution + as coexisting ions), NaF (free F in the test solution - As coexisting ions), NaNO3 (free NO3 in the test solution - As coexisting ions), Na2SO4 (free SO4 in the test solution2- As coexisting ions), NaH2PO4 (free HPO4 in the test solution - As coexisting ions), Na2CO3 (free CO3 in the test solution 2- As coexisting ions), NaHCO3 (free HCO3 in the test solution - as coexisting ions), humic acid (HA) and NaAC (AC is released in the test solution) - As one of the coexisting ions), the salt concentration in the test solution is 10mmol / L, and the test results are as follows Figure 4 As shown by Figure 4 It can be seen that the coexisting ions have no significant effect on the removal rate of aniline.

[0068] The cobalt-doped zinc oxide nanocatalyst prepared in Example 3 was used as a "catalyst" to carry out the "pollutant removal experiment" in Example 5 above on the pollutant solution (the pollutant was aniline, and the pH was 3, 5, 7 and 9, respectively). The pH was adjusted by 0.1 mol / L hydrochloric acid or 0.1 mol / L sodium hydroxide aqueous solution. The removal rate and reaction rate constant of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 are shown in FIG. Figure 5 As shown by Figure 5 It can be seen that in the pH range of 3 to 11, the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 has an excellent removal rate for aniline and also has a relatively high reaction rate constant, both of which are within 0.8 min -1 Above, the highest is 1.6351min -1 When pH is 7, the reaction rate constant is 1.4785min -1 , is the zinc oxide catalyst prepared in Example 1 (when pH is 7, the reaction rate constant is 0.04346min -1 ), combined with Figure 4 and Figure 5 It can be seen that the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 is little affected by common environmental matrices in real water bodies.

[0069] Example 7

[0070] The degradation selectivity of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 for common pollutants was explored. Referring to the pollutant removal experiment using the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 as a "catalyst" in Example 5, the aniline in the pollutant solution was replaced with any one of rhodamine B (RhB), methylene blue (MB), aniline (AN), tetracycline (TC), doxycycline hydrochloride (DOXH), o-aminophenol (O-PA), carbamazepine (CBZ), acetaminophen (APAP), sulfachloropyridazine (SCP), sulfamethoxazole (SMX), o-nitrophenol (O-NP), p-nitrophenol (P-NP), nitrobenzene (NB) and benzoic acid (BA) as the pollutant, the initial concentration (C0) of the pollutant in the pollutant solution was 10 mg / L, the pH of the pollutant solution was 7, and the removal rate of each pollutant by the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 was as follows: Figure 6 shown.

[0071] Depend on Figure 6 It can be seen that pollutants containing electron donating groups (EDGs) such as hydroxyl, amino, methyl, halogen or organic sulfide groups can be more effectively removed by the cobalt-doped zinc oxide nanocatalyst prepared in Example 3, and the removal rates of RhB, MB, AN, TC, DOXH, O-PA, CBZ and APAP are all above 80.0%. In contrast, the removal rate of O-NP and P-NP with both EDGs and electron withdrawing groups (EWGs) prepared in Example 3 by the cobalt-doped zinc oxide nanocatalyst is reduced, while the removal rate of pollutants containing electron withdrawing groups such as carboxyl and -NO2 is poor, and NB and BA are difficult to remove, with removal rates of only 16.7% and 12.2%, respectively. The above results show that the cobalt-doped zinc oxide nanocatalyst has higher selectivity and reactivity for pollutants containing electron donating groups.

[0072] Example 8

[0073] Referring to the pollutant removal experiment using the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 as a "catalyst" in Example 5, the pollutant solution was replaced with actual sewage (from the Jinnan Sewage Treatment Station of Nankai University) for qualitative analysis.

[0074] The actual sewage before and after the above degradation was subjected to three-dimensional excitation emission matrix (3D-EEM) fluorescence spectrum test, and the results are as follows: Figure 7 As shown by Figure 7 As shown in (a), a fluorescence peak was observed near the excitation wavelength / emission wavelength (Ex / Em) = 285 / 335 nm (e.g. Figure 7 The fluorescence peak (shown as "I" in (a)) corresponds to tryptophan, and a fluorescence peak ( Figure 7The corresponding protein is an aromatic protein, and a fluorescence peak is observed near Ex / Em=340 / 425nm ( Figure 7 The fluorescence peak (shown as "III" in (a)) corresponds to humic acid, and a fluorescence peak ( Figure 7 The "IV" in (a) corresponds to fulvic acid substances. Therefore, the actual sewage contains tryptophan, aromatic protein, humic acid and fulvic acid substances. Figure 7 (b) shows that after the degradation of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3, the intensity of the fluorescence peaks in these EEMs is significantly reduced, especially the peaks related to aromatic proteins, which indicates that the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 can effectively reduce difficult-to-degrade substances in actual sewage.

[0075] Example 9

[0076] 10 mg of catalyst (the catalyst is the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 or the Co-doped ZnO catalyst prepared in Comparative Example 2) and 50 mL of pollutant solution were placed in a 100 mL beaker and stirred for 30 min. After stirring, 15 mg of PMS was added to obtain a test solution. The test solution was stirred for 10 min at 25° C. for degradation. The test solution was taken at T1 min of degradation to test the Co metal ion concentration. T1 min was 0 min, 5 min and 10 min, respectively. The test results are as follows: Figure 8 As shown by Figure 8 It can be seen that after adding PMS to degrade for 10 minutes, the Co metal ion concentration in the test solution containing the Co-doped ZnO catalyst prepared in Comparative Example 2 is as high as 31.05 mg / L, which indicates that the Co-doped ZnO catalyst prepared in Comparative Example 2 has poor structural stability, and a large amount of Co metal ions leak during use, causing secondary pollution, and is difficult to be directly applied to the environmental water purification process. The Co-doped zinc oxide nanocatalyst prepared in Example 3 has a Co metal ion concentration leakage of 0.5169 mg / L when PMS is not added, which is low. After adding PMS to degrade for 10 minutes, it may be Co metal ions (Co 2+ ) promotes the transfer of 2 electrons to react with PMS to produce Co IV =O, so that the concentration of Co metal ions in the test solution is only 0.1273 mg / L, which is far lower than 1 mg / L specified in the "Copper, Nickel and Cobalt Industrial Pollutant Emission Standard" (GB25467-2010). This shows that the cobalt-doped zinc oxide nanocatalyst of the present invention has high structural stability and environmental friendliness.

[0077] Example 10

[0078] The cobalt-doped zinc oxide nanocatalyst (dosage = 10 mg) prepared in Example 3, the Co-doped ZnO catalyst (dosage = 10 mg) prepared in Comparative Example 2, and cobalt nitrate hexahydrate were used as "catalysts" to carry out the pollutant removal experiment in Example 5. When cobalt nitrate hexahydrate was used as the "catalyst", the concentrations of cobalt nitrate hexahydrate in the test solution were 0.1273 mg / L and 31.05 mg / L (designed according to the Co metal ion leakage during degradation for 10 min), respectively. The test results are as follows: Fig. 9 As shown, the test results of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 are as follows Fig. 9 As shown in "Example 3 (10 mg)", the test results of the Co-doped ZnO catalyst prepared in Comparative Example 2 are as follows Fig. 9 As shown in "Comparative Example 2 (10 mg)", the test results of cobalt nitrate hexahydrate with a concentration of 0.1273 mg / L are as follows Fig. 9 As shown in "Cobalt nitrate hexahydrate (0.1273 mg / L), the test results of cobalt nitrate hexahydrate with a concentration of 31.05 mg / L are as follows Fig. 9 "Cobalt nitrate hexahydrate (31.05 mg / L)"

[0079] Depend on Fig. 9 It can be seen that at 5 min, the removal rate of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 was 100%, and the removal rate of the Co-doped ZnO catalyst prepared in Comparative Example 2 was 98%, both of which were very high. The removal rate using 31.05 mg / L cobalt nitrate hexahydrate was almost the same as the removal rate of the Co-doped ZnO catalyst prepared in Comparative Example 2, indicating that the Co-doped ZnO catalyst prepared in Comparative Example 2, as a Fenton-like catalyst, activated PMS to degrade aniline, mainly relying on its leaked Co metal ions to activate PMS for degradation. When the concentration of cobalt nitrate hexahydrate is 0.1273 mg / L, the removal rate of aniline within 5 minutes is almost only 4.7%, which indicates that the Co metal ion leakage of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 has little effect on the removal rate. The cobalt-doped zinc oxide nanocatalyst prepared in Example 3 itself has a high removal rate for aniline. Under the same catalyst mass, the Co ion doping amount in the Co-doped ZnO catalyst prepared in Comparative Example 2 is much higher than that of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3. Therefore, the present invention achieves a significant improvement in catalyst performance by constructing a localized dipole through an extremely low Co ion doping amount.

[0080] The content of metallic cobalt in the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 and the Co-doped ZnO catalyst prepared in Comparative Example 2 was measured using an inductively coupled plasma mass spectrometer (ICP-MS). The cobalt content in the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 was 3.06wt%, and the cobalt content in the Co-doped ZnO catalyst prepared in Comparative Example 2 was 25.08wt%. Therefore, under the same cobalt mass as 10mg of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 (the mass of the Co element contained was about 0.3mg), 1.2mg of the Co-doped ZnO catalyst prepared in Comparative Example 2 (the mass of the Co element contained was 0.3mg) was taken as the "catalyst" to carry out the pollutant removal experiment in Example 5. The results are as follows: Fig. 9 As shown in "Comparative Example 2 (1.2 mg)", under the same Co element mass, the removal rate of the Co-doped ZnO catalyst prepared in Comparative Example 2 is only 25%.

[0081] Embodiment 11

[0082] capture 1 The O2 experiment set up the following experimental groups:

[0083] Catalyst group: 10 mg of catalyst, 15 mg of PMS, capture agent and 50 mL of pollutant solution were placed in a 100 mL beaker to obtain a mixed solution. The mixed solution was stirred for 5 min at 25 °C and then detected by Bruker A200 electron paramagnetic resonance (EPR) spectrometer. 1 O2, wherein the catalyst is one of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 and the zinc oxide catalyst prepared in Comparative Example 1, the capture agent is 2,2,6,6-tetramethylpiperidine, and the concentration of 2,2,6,6-tetramethylpiperidine in the mixed solution is 30 μmol / L. The test results are as follows Fig.10 As shown in (a);

[0084] PMS Group: As with the above “capture 1 The catalyst group of the "O2 experiment" is basically the same, the difference is the mixed solution, PMS, capture agent and 50mL pollutant solution are placed in a 100mL beaker to obtain a mixed solution, the concentration of PMS in the mixed solution is 0.3mg / mL, the test results are as follows Fig.10 As shown in (a).

[0085] High-valent oxygenated cobalt (Co IV =O) Experimental setup The following experimental groups:

[0086] Catalyst group: "Co IV =O experiment" catalyst group and "capture 1The catalyst groups of the "O2 experiment" were basically the same, except for the capture agent and stirring time. The capture agent was methyl phenyl sulfoxide (PMSO), and the initial concentration (C0) of PMSO in the mixed solution was 100 μmol / L. The mixture was stirred for 10 min, and the concentration of PMSO (C0) was measured by Thermo Fisher Dionex UltiMate U3000 HPLC at T2 min. t ), T2min is 0min, 1min, 2min, 3min, 5min, 7min, 10min, and PMSO consumption (ΔPMSO = C t -C0), due to PMSO and Co IV =O, so the PMSO consumption can be used to determine Co IV =O is generated, and the test results are as follows Fig.10 as shown in (b);

[0087] PMS group: Same as the above “Co IV =O experiment" is basically the same, except that the mixed solution does not contain a catalyst, that is, PMS, capture agent and 50mL pollutant solution are placed in a 100mL beaker to obtain a mixed solution, the concentration of PMS in the mixed solution is 0.3mg / mL, and the initial concentration (C0) of PMSO in the mixed solution is 100μmol / L. The test results are shown in Fig.10 as shown in (b).

[0088] Depend on Fig.10 (a) shows that in "capture 1 O2 experiment". No results were detected in the PMS group. 1 The characteristic signal of O2 was detected in the mixed solution of zinc oxide catalyst prepared in comparative example 1 in the catalyst group. 1 The characteristic signal of O2, the mixed solution of cobalt-doped zinc oxide nanocatalyst prepared in Example 3 detected a stronger 1 O2 characteristic signal, which shows that the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 can more efficiently activate PMS to produce 1 O2. By Fig.10 As shown in (b), the mixed solution of cobalt-doped zinc oxide nanocatalyst prepared in Example 3 detected more PMSO consumption, which shows that cobalt-doped zinc oxide nanocatalyst can more efficiently activate PMS to produce 1 O2 and Co IV =O.

[0089] Example 12

[0090] Fig.11 (a) is the electron localization function (ELF) calculation diagram of the zinc oxide catalyst prepared in Comparative Example 1, Fig.11 (b) is the ELF calculation diagram of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3. Fig.11 (a) and (b)) show that, as confirmed by atomic charge analysis, the Bader charge of the Co atomic site in the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 is +0.805e, and the Bader charge of the adjacent Zn atomic site is +1.056e, while the Bader charge of the Zn atomic site in the zinc oxide catalyst prepared in Comparative Example 1 is +0.906e, indicating that compared with the zinc oxide catalyst prepared in Comparative Example 1, the charge density distribution of the cobalt-doped zinc oxide nanocatalyst prepared in Example 3 is asymmetric, and the charge density distribution of the Co atomic site is higher than that of the adjacent Zn atomic site. This is due to the different electronegativity between the metal atoms Zn and Co and the O atom, and bond dipole moments are formed on the Zn-O and Co-O bonds. The vector superposition of the bond dipole moments will form a local dipole in the adjacent annular region of the central metal site to produce a dipole effect (such as Fig.11 As shown in (c), the charge density difference between the Co and Zn atomic sites is caused. The dipole effect effectively adjusts the electron density of Co and the surrounding Zn atoms, breaking the original charge balance and forming positive (Zn atomic site) and negative (Co atomic site) polarized charge centers. The polarized charge centers at the Zn atomic site promote the self-decomposition of the two PMS molecules, producing highly selective 1 The polarized charge center at the Co atomic site promotes the 2 electron transfer to produce Co IV =O, so the cobalt-doped zinc oxide nanocatalyst regulates PMS activation depends on 1 O2 and Co IV =O synergistically, it exhibits high catalytic activity towards electron-rich pollutants.

[0091] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A method for preparing a cobalt-doped zinc oxide nanocatalyst, characterized in that: The following steps are involved: Step 1, dissolving zinc salt and citric acid in deionized water, adding cobalt salt and mixing evenly, stirring at room temperature of 15-25° C. for 1-1.5 hours to obtain a sol liquid, reacting the sol liquid at 70-80° C. for 3-4 hours to obtain a wet gel, drying the wet gel at 160-180° C. for 3-3.5 hours, grinding, and obtaining a precursor powder, wherein, by amount of substance, the ratio of zinc in the zinc salt, cobalt in the cobalt salt, and citric acid is 15: (0.75-1.05): 45; Step 2: calcining the precursor powder at 480-520° C. for 5-5.5 h in an air atmosphere, washing, and drying to obtain a cobalt-doped zinc oxide nanocatalyst.

2. The preparation method according to claim 1, characterized in that: The ratio of the amount of zinc in the zinc salt to the volume of deionized water is 1:(25-35), the unit of the amount of zinc is mmol, and the unit of the volume is mL.

3. The preparation method according to claim 1, characterized in that: The zinc salt is zinc nitrate hexahydrate, and the cobalt salt is cobalt nitrate hexahydrate.

4. The preparation method according to claim 1, characterized in that: The grinding time is 4 to 6 minutes.

5. The preparation method according to claim 1, characterized in that: Heat to 480-520°C at a rate of 4-6°C / min.

6. The preparation method according to claim 1, characterized in that: The washing operation comprises: centrifuging at least three times with water and ethanol at a speed of 8000-10000 r / min, each centrifuging for 3-5 minutes.

7. The preparation method according to claim 1, characterized in that: The drying temperature is 60-80°C.

8. The preparation method according to claim 1, characterized in that: The drying time is 10 to 12 hours.

9. The cobalt-doped zinc oxide nanocatalyst obtained according to the preparation method according to any one of claims 1 to 8.

10. Use of the cobalt-doped zinc oxide nanocatalyst according to claim 9 in removing pollutants.

Citation Information

Patent Citations

  • Macro preparation method for carbon doped zinc oxide-based visible-light catalyst

    CN104148047A

  • Method for preparing cobalt-doped zinc oxide nanorods through sol-gel

    CN105314672A

  • Application of Al-Ce codoping in improving photocatalytic properties of ZnO micro-powder

    CN106311209A

  • Co-doped ZnO catalyst and preparation method and application thereof

    CN113976125A

  • Method for catalyzing organic pollutants by activating PMS through A-site lanthanum-doped lithium cobalt oxide

    CN118079938A

Cited By

  • Porous Cudelta+ / ZnO / Al2O3 catalyst based on sol template confinement anchoring as well as preparation method and application of porous Cudelta+ / ZnO / Al2O3 catalyst

    CN121775847A